The Influence of Realistic Mathematics Learning Approach Based on Local Wisdom of Simalungun Ethnic Group on Students' Mathematical Problem Solving Ability - Prasojo, Riki; Napitulu, E. Elvis; Simamora, Elmanani (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
This study aims to analyze: (1) The differences in mathematical problem-solving abilities of students taught with the PMR approach based on the local wisdom of the Simalungun ethnic group and the conventional approach; (2) The interaction between the learning approach and KAM on students' problem-solving abilities. This study is a quantitative study with a quasi-experimental method. The population in this study were all students of Tunas Harapan Private Middle School in the 2023/2024 Academic Year, totaling 200 people. The sampling technique for this study used a purposive sampling technique by selecting classes VIII-1 and VIII-2 as samples to be studied, totaling 50 people. The instruments used in this study were descriptive tests and questionnaires. The test was carried out with Two-Way ANOVA. The results of the study showed that (1) The problem-solving abilities of students in the PMR approach class based on the local wisdom of the Simalungun ethnic group were better than those in the ordinary learning approach class; (2) There was no interaction between the learning approach and initial mathematical abilities (high, medium, and low) on students' mathematical problem-solving abilities.